Evaluation of the impact of a digital care navigator on increasing patient registration with digital mental health interventions in routine care - Brittany Jaso-Yim; Mara Eyllon; Pratha Sah; Mariesa Pennine; George Welch; Keke Schuler; Laura Orth; Heather O'Dea; Elizabeth Rogers; Lily H. Murillo; J. Ben Barnes; Georgia Hoyler; et al. (Internet Interventions)
Background: Less than half of adults with mental health disorders in the United States receive appropriate or timely care. Digital Mental Health Interventions (DMHIs) have the potential to bridge this gap. However, real-world adoption of DMHIs is impeded by patient and provider-level technological barriers. Care navigators have the potential to address these challenges by providing technical support and enhancing patients' experience with DMHIs. Objective: This study explores the effect of a digital care navigator (DCN) on patient registration latency and rates of DMHIs implemented as part of a digital-first behavioral health care model integrated within routine care at a large multispecialty group medical practice. Methods: Data were collected from electronic medical records and DMHI registration data were obtained from the DMHI vendors. Descriptive statistics were used to describe the DCN's efforts to help patients register with their DMHIs. Moods median tests evaluated differences in registration latency and weekly registration rate pre- and post- DCN implementation. Change in registration likelihood as a function of DCN outreach latency was investigated using a Kaplan-Meier plot. Results: During the first eight months, the DCN made 1306 phone calls to 680 unique patients, successfully connecting with 66 %. DCN implementation also increased the median registration rate from 61.9 % to 76.9 %. Results showed that the expediency by which the DCN outreached patients directly impacted registration rate such that of those who were outreached by the DCN on the day of their referral to a DMHI, 96.86 % registered. This number was reduced to 76.15 % if the DCN reached them 1-day following referral, and 41.39 % 5-days after their referral. Conclusions: Use of a DCN shows promise for enhancing patient registration rates with DMHIs in routine healthcare settings.